PRZESTĘPSTWA I KARY W REGULACJACH PRAWNYCH NOWOANGIELSKICH KOLONII W AMERYCE PÓŁNOCNEJ W XVII WIEKU - Maćkowska, Katarzyna (Zeszyty Prawnicze, 2016)
CRIMES AND PUNISHMENTS IN LEGAL REGULATIONS OF NEW ENGLAND COLONIES IN THE 17TH CENTURY Summary The subject of this article pertains to a colonial criminal law of New England colonies in 17th century. There are few studies on this matter, however the dominating aspects relates to a history of constitutional solutions. Comparison between normative aspect and examples of their application undoubtedly confirms some undemocratic background of colonial life. Moreover, contemporary interest in historical sciences seems to be increasing what should be sufficient reason for refreshing the older researches. Although New England colonies were founded under specific circumstances implied by relation between state and religion, they manager to set up a public system of criminal law. Nonetheless, colonists, while mainly focused on constitutional basis for their self-government, they used English and biblical paradigms for criminal regulations. One may find, however, that colonial documents consisted of rules describing a meaning of selected crimes and created relatively systematic catalogues. Detailed problems here analyzed are as following: general features of colonial criminal laws, crimes against a state and a government, against religion, against an individual and a property, against a family, crimes connected to administrative indications and selected instances of penalties.